2019
DOI: 10.1088/1757-899x/662/2/022107
|View full text |Cite
|
Sign up to set email alerts
|

Develop Accounting Information Systems of Sales in Village-Owned Enterprise

Abstract: The purpose of this research is to develop a sale accounting information system in the Village-Owned Enterprises (BUM Desa Satia), especially sales which are source of income. Financial reporting standards use Indonesian Accounting Standards for Entities without Public Accountability (ETAP). This study used a descriptive qualitative study approach and method for developing sales accounting information systems in the Village Owned Enterprise using the Accelerated SAP (ASAP) approach. The results of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…That way, the Accurate application can maintain its main properties, namely easy use (user friendly) and high accuracy, which will give satisfaction to the user (Firdaus, D. W. 2019).…”
Section: H Transaction Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…That way, the Accurate application can maintain its main properties, namely easy use (user friendly) and high accuracy, which will give satisfaction to the user (Firdaus, D. W. 2019).…”
Section: H Transaction Controlmentioning
confidence: 99%
“…SQL stands for Structured Query Language, being the language for extracting information from data (Rosa, D., & Purfini, A. P. 2019). Client/Server Technology with rollback capability (Firdaus, D. W. 2019). Client/Server Technology is built into a network that covers two connected computers such as the server and the client.…”
Section: Accurate Technologymentioning
confidence: 99%
“…Research conducted by Maulana [11], who implemented Odoo MRP (Material Requirement Planning) which contains Inventory and Warehouse [8] module for raw material inventory in controlling the production process for a manufacturing company, found that this MRP facilitates the smooth production process such as safety stock, then to systematically control the company is recommended use Odoo Manufacturing system module. Besides module of inventory management and material requirement planning, application of ERP at BUMDes also customization of accounting module, as conducted by Firdaus [12], by using a sales accounting information system using Odoo, it is expected BUMDes to be able to manage financial transactions and investment decisions.…”
Section: Enterprise Resource Planning Systemmentioning
confidence: 99%